Environmental implications of one-century COPRs evolution in a single industrial site: From leaching impact to sustainable remediation of CrVI polluted groundwater. (November 2021) - Molinari, Simone; Magro, Massimiliano; Carbone, Cristina; Baratella, Davide; Ugolotti, Juri; Ianni, Maria Carmela; Badocco, Denis; Canepa, Marco; Zboril, Radek; Vianello, Fabio; Salviulo, Gabriella
Abstract: The Stoppani factory manufactured chromium for more than one century, dumping millions of tons of Chromite Ore Processing Residues (COPRs) over decades. The massive presence of COPRs resulted in an intense Cr VI leaching and consequent contamination of percolating groundwater. The site offers a unique opportunity to follow COPRs evolution from the primary roasting process to the aged Cr-bearing mineral phases. Herein, new insights on COPRs mineralogy evolution and their role in Cr VI release are provided by a dry sample preparation protocol, coupled with in-depth multi-technique characterization. Besides typical COPRs mineral assemblages, highly soluble Na2 CrO4 and the first evidence of crocoite (PbCrO4 ) in a COPR contaminated site are revealed. Selective extraction experiments confirmed a strong reactivity for Cr-bearing minerals as confirmed by concentrations as high as 375 mg L −1 of leached Cr VI . The mineralogical approach was combined with a nanotechnological solution for Cr VI wastewater remediation. The application of naked colloidal maghemite (γ-Fe2 O3 ) nanoparticles (SAMNs) on the complex industrial wastewater, led to > 90% Cr VI removal, either under acidic or in-situ conditions. The present case study of a highly polluted site, ranging from mineral characterization to wastewater remediation, highlights the use of multidisciplinary approaches to cope with complex environmental issues. Highlights: New insights on the evolution and identification of different aged COPRs. Dry sample preparation led to preservation of all Cr VI -bearing minerals. A new COPR Cr VI host mineral, Crocoite (PbCrO4 ), was identified. Novel sulphate-chromate competition on nanosized γ-Fe2 O3 . SAMNs represent a sustainable candidate for industrial wastewater remediation.